2016
DOI: 10.5114/pdia.2016.56930
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of systemic inflammation with neutrophil-lymphocyte ratio in lichen planus

Abstract: IntroductionLichen planus (LP) is a papulosquamous eruption of the skin and mucous membranes. Although the exact pathogenesis of the disease remains unclear, it is believed that LP represents an inflammatory disorder. Neutrophil-lymphocyte (N/L) ratio is considered a systemic inflammatory marker that correlated with severity of the diseases.AimTo investigate whether N/L ratio increases in LP and may be an independent severity marker for LP lesions.Material and methodsWhite blood cell (WBC), neutrophil and lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Zaragoza et al 20 reported that an increasing initial NLR value may be independently associated with specific mortality in Merkel cell carcinoma. Atas et al 21 found that ESR, CRP and NLR were statistically higher in patients with lichen planus when compared with the controls. Karabay et al 22 compared the CRP, MHR and CBC parameters in the psoriasis and control group and observed statistically significantly higher CRP, MHR, NLR and MLR values in the psoriasis group compared to the control group.…”
Section: Discussionmentioning
confidence: 96%
“…Zaragoza et al 20 reported that an increasing initial NLR value may be independently associated with specific mortality in Merkel cell carcinoma. Atas et al 21 found that ESR, CRP and NLR were statistically higher in patients with lichen planus when compared with the controls. Karabay et al 22 compared the CRP, MHR and CBC parameters in the psoriasis and control group and observed statistically significantly higher CRP, MHR, NLR and MLR values in the psoriasis group compared to the control group.…”
Section: Discussionmentioning
confidence: 96%
“…Zaragoza et al reported that an increased initial NLR value in Merkel cell carcinoma may be independently associated with specific mortality . Atas et al found that ESR, CRP, and NLR were statistically higher in patients with lichen planus compared with controls …”
Section: Discussionmentioning
confidence: 99%
“…The relationship has, to date, only been investigated in a disease-specific manner, most comprehensively among psoriasis patients (7,11,12): an extensive meta-analysis of data from such studies has shown that CRP levels are elevated in patients with psoriasis compared with healthy subjects (7). Studies with limited sample size have showed that low grade inflammation is also present in chronic urticaria (n = 58) (13), lichen ruber planus (n = 55) (14) and rosacea (n = 60) (15). Recent studies have demonstrated that children and young adults with atopic eczema or allergic sensitization have elevated CRP levels (16)(17)(18).…”
mentioning
confidence: 99%